Identifikasi Struktur Geologi Bawah Permukaan Pada Area Panas Bumi Gunung Talang-Bukit Kili Berdasarkan Data Gaya Berat GGMPlus - Herlan; M. Sepbastian Veron; Purwaditya Nugraha; Nugroho Prasetyo; Fajar Adivadilah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to identify subsurface geological structures in the Gunung Talang– Bukit Kili geothermal area, West Sumatra, using GGMPlus gravity data. The data were processed through latitude, free-air, Bouguer, and terrain corrections to produce the Complete Bouguer Anomaly (CBA). Spectral analysis indicates that the depth of the regional anomaly source is in the range of 10000 m. The Tilt Derivative (TDR) and Normalized Horizontal Tilt Derivative (TDX) methods were applied to delineate geological structural boundaries. Two dimensional forward modeling along a 24 km profile with a depth of 10 km shows rock density variations between 1,800–2,500 kg/m³, representing volcanic rocks, altered sediments, and metamorphic basement rocks. The 2D forward modeling identifies a northwest–southeast trending fault zone that acts as a pathway for hydrothermal fluid migration.